Managers’ Responses To Singapore’s Foreign Labor Policy: A Study Of The Manufacturing And Manufacturing Related Services Sectors - Wattanatinnachot, Khemmanit (2020)
The thesis is a study of managers’ responses to Singapore’s foreign labor policy in the context of the manufacturing and manufacturing related services sectors. The study adopted structuration theory to describe and explain the interaction of different actors such as the state, foreign workers and managers. The study provided an understanding of industrial relations in Singapore, particularly the role of the state in shaping its industrial and foreign labor policy. The study adopted twenty-five semi-structured interviews from managers in five different manufacturing industries, namely the electronics, chemical, biomedical engineering, precision engineering and transportation engineering industries. The study showed that managers’ choices of hiring were shaped by Singapore’s foreign labor policy when hiring R Pass and S Pass workers in the manufacturing sector compared to the manufacturing related services sector.